Role of career adaptability and its resources in predicting vocational attitudes of Indian IT professionals - Santra, Sayoni; Giri, V.N. (2019)
Indian Information Technology (IT) market is going through a dynamic state of existence with employment uncertainties, but simultaneously creating promising opportunities. Amidst such unpredictability and possibilities, Indian IT professionals have been striving hard to build a career identity, demonstrating their capabilities to withstand unforeseen and abrupt vocational shocks. In career construction, such capability comes from career adaptability, reflected through resources of concern, control, curiosity and confidence. Yet, attention towards career adaptability is sparse in Indian IT vocational literature. The present study attempts to fill that gap by examining career adaptability and its links with vocational attitudes of career satisfaction and turnover intention. For this, data were collected from 434 Indian IT professionals. Overall, career adaptability was positively related to career satisfaction while turnover intention was independent of it. At the dimensional level, independently, all resources of career adaptability were positively related to career satisfaction. Concern and confidence had relatively greater degree of positive association than curiosity and control. Further, concern led to increased turnover intention, other resources being unrelated to it. Findings may facilitate human resource management of Indian IT organizations and independent career practitioners to enhance the vocational success of their employees and clients. - Reproduced.
Keywords: Job satisfaction